ECHO CHAMBERS DI DUNIA MAYA: TANTANGAN BARU KOMUNIKASI ANTAR UMAT BERAGAMA - Yuangga Kurnia Yahya; Umi Mahmudah (UIN Sunan Kalijaga Yogyakarta, 2019)
This article tries to see a phenomenon called Echo Chambers through the perspective of Stella Ting-Toomey’s Intercultural Communication Theory. This study shows that the development of social media was also followed by the shadow of Echo Chambers. The tendency to isolate oneself and associate with those who understand one another will create separate spaces between one religion and another. As a result, communication which is an effort to eliminate the polarization of the differences between